Modelagem matemática por meio de Sistemas Fuzzy: um Instrumento para avaliação de autismo - Zago, Lucas de Agostini (Universidade Federal de São Carlos, 2019)
In this work, concepts, definitions and theorems about Fuzzy Logic and Systems Based on Fuzzy Rules were presented. We used these systems to develop a mathematical model for diagnosing autism based on the CARS-BR scale: without autism, mild / moderate autism, and severe autism. The choice is due to the great subjectivity involved in the medical diagnosis process of behavioral syndromes.
Mathematical modeling through Fuzzy systems: an instrument for assessing autism
Keywords: Conjuntos Fuzzy; Sistemas Fuzzy; Autismo; Modelagem Matemática; Sistemas difusos; Fuzzy Systems; Autism; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA